Rhinovirus C is associated with wheezing and rhinovirus A is associated with pneumonia in hospitalized children in Morocco. Issue 4 (30th September 2016) - Annamalay, Alicia A.; Jroundi, Imane; Bizzintino, Joelene; Khoo, Siew‐Kim; Zhang, Guicheng; Lehmann, Deborah; Laing, Ingrid A.; Gern, James; Goldblatt, Jack; Mahraoui, Chafiq; Benmessaoud, Rachid; Moraleda, Cinta; et al.
Abstract : Human rhinovirus (RV) is commonly associated with severe acute lower respiratory infections (ALRI) in children. We aimed to describe the distribution of RV species and associations between RV species and clinical features in children hospitalized with clinically severe pneumonia (CSP) in Morocco. Nasopharyngeal aspirates (NPAs) were collected from 700 children, 2–59 months of age, admitted with CSP to the Hôpital d'Enfants de Rabat in Morocco. At least one respiratory virus was identified in 92% of children, of which RV was the most common (53%). PCR assays, sequencing, and phylogenetic tree analyses were carried out on 183 RV‐positive NPAs to determine RV species and genotypes. Of 157 successfully genotyped NPAs, 60 (38.2%) were RV‐A, 8 (5.1%) were RV‐B, and 89 (56.7%) were RV‐C. Wheezing and cyanosis were more common in RV‐C‐positive than RV‐A‐positive children (80.9% vs. 56.7%; P  = 0.001 for wheezing and 10.1% vs. 0%; P  = 0.011 for cyanosis). Physician's discharge diagnosis of pneumonia was more frequent among RV‐A‐positive (40.0%) than RV‐C‐positive children (20.2%; P  = 0.009). RV‐A and RV‐C showed distinct seasonal patterns. Our findings suggest that RV‐C is associated with wheezing illness while RV‐A is associated with pneumonia. J. Med. Virol. 89:582–588, 2017 . © 2016 Wiley Periodicals, Inc.